Evaluasi Formatif Program Pemberdayaan Fakir Miskin (P2FM) melalui Bantuan Langsung Pemberdayaan Sosial (BLPS) (Studi di KUBE Dasa Manunggal, Kecamatan Minggir, Kabupaten Sleman) - , Nuraeni Dramayanti, S.Sos, Prof. Dr. Agus Dwiyanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study aimed at conducting a formative evaluation of the implementation of Program Pemberdayaan Fakir Miskin melalui mekanisme Bantuan Langsung Pemberdayaan Sosial (P2FM-BLPS) in KUBE Dasa Manunggal representing one of the KUBE models in Sleman district. The formative evaluation of the P2FM-BLPS consisted of 3 aspects, which were the extent to which the P2FM-BLPS has met the right target, the consistency and the clarity in delivering services with program design specification and formal objective/target after the implementation of the P2FM-BLPS. The study used qualitative approach in the location of KUBE Dasa Manunggal in Balangan community of Sendangrejo village, Minggir subdistrict of Sleman district. The KUBe was chosen on the consideration that the KUBE Dasa Manunggal has been the beneficiary of the P2FM-BLPS since 2007 in which the program was firstly initiated. There were 14 informants consisting of the board members and the members of the KUBE Dasa Manunggal (10 individuals), a village assistant, two district assistants and a province assistant. The results of the study showed that the implementation of the P2FM-BLPS in the KUBE Dasa Manunggal has not been in accordance with the program as contained in the P2FM-BLPS guideline. The target groups have not met the criteria of the P2FM-BLPS. The aspects of clarity and consistency in delivering the service with the program spesification have not been maximal. It could be clearly observed in the formulation of the intervention strategy and the activity component/activity instrument that have not been well-understood by the target groups. Additionally, the timing in giving the business capital grant was not appropriate, the assistance was more administrative in nature while there was not enough assistance related to the management of the grant, and those in poverty have not benefited from the monitoring activity. The objectives/the formal targets of the P2FM-BLPS have not been met as indicated by the increase in income though the business of the KUBE Dasa Manunggal experienced a little bit development in addition to the increase in the social activity of the members of the KUBE Dasa Manunggal. In general, it was still necessary to improve the implementation of the P2FM-BLPS. The clarity and the consistency in delivering the services with the program design spesification played an important role in the empowerment of those in poverty and hence it was necessary for the implementing organization and the target groups to use intervention strategy at applicating activity level and not merely at socialization activity level. It was necessary to improve the coordination of the implementing organizations, which were Ministry of Social Affair of Republic of Indonesia, Province Social Office, District Social Office that they did not blame each other in the implementation of the activity component/activity instrument in order to timely implement the program for the right target groups. It was also necessary to base the implementation of the P2FM-BLPS on cooperation agreement with other parties especially in providing the KUBE with the opportunity to develop their business because there were those in poverty who still faced difficulties in developing their business because of the presence of other policies that did not stand up for them.